Olfactory Loss and Dysfunction in Ciliopathies: Molecular Mechanisms and Potential Therapies - Uytingco, Cedric R.; Green, Warren W.; Martens, Jeffrey R. (Current Medicinal Chemistry, 2019)
Background: Ciliopathies are a class of inherited pleiotropic genetic disorders in which alterations in cilia assembly, maintenance, and/or function exhibit penetrance in the multiple organ systems. Olfactory dysfunction is one such clinical manifestation that has been shown in both patients and model organisms. Existing therapies for ciliopathies are limited to the treatment or management of symptoms. The last decade has seen an increase in potential curative therapeutic options including small molecules and biologics. Recent work in multiciliated olfactory sensory neurons has demonstrated the capacity of targeted gene therapy to restore ciliation in terminally differentiated cells and rescue olfactory function. This review will discuss the current understanding of the penetrance of ciliopathies in the olfactory system. Importantly, it will highlight both pharmacological and biological approaches, and their potential therapeutic value in the olfactory system and other ciliated tissues. Methods: We undertook a structured and comprehensive search of peer-reviewed research literature encompassing in vitro, in vivo, model organism, and clinical studies. From these publications, we describe the olfactory system, and discuss the penetrance of ciliopathies and impact of cilia loss on olfactory function. In addition, we outlined the developing therapies for ciliopathies across different organ and cell culture systems, and discussed their potential therapeutic application to the mammalian olfactory system. Results: One-hundred sixty-one manuscripts were included in the review, centering on the understanding of olfactory penetrance of ciliopathies, and discussing the potential therapeutic options for ciliopathies in the context of the mammalian olfactory system. Forty-four manuscripts were used to generate a table listing the known congenital causes of olfactory dysfunction, with the first ten listed are linked to ciliopathies. Twenty-three manuscripts were used to outline the potential of small molecules for the olfactory system. Emphasis was placed on HDAC6 inhibitors and lithium, both of which were shown to stabilize microtubule structures, contributing to ciliogenesis and cilia lengthening. Seventy-five manuscripts were used to describe gene therapy and gene therapeutic strategies. Included were the implementation of adenoviral, adeno-associated virus (AAV), and lentiviral vectors to treat ciliopathies across different organ systems and application toward the olfactory system. Thus far, adenoviral and AAVmeditated ciliary restoration demonstrated successful proof-of-principle preclinical studies. In addition, gene editing, ex vivo gene therapy, and transplantation could serve as alternative therapeutic and long-term approaches. But for all approaches, additional assessment of vector immunogenicity, specificity, and efficacy need further investigation. Currently, ciliopathy treatments are limited to symptomatic management with no curative options. However, the accessibility and amenability of the olfactory system to treatment would facilitate development and advancement of a viable therapy. Conclusion: The findings of this review highlight the contribution of ciliopathies to a growing list of congenial olfactory dysfunctions. Promising results from other organ systems imply the feasibility of biologics, with results from gene therapies proving to be a viable therapeutic option for ciliopathies and olfactory dysfunction.
Keywords: ciliopathy